The Influence of Organization Culture and Organization Structure on the Implementation of Innovation Process in Telkom Divisi Digital Service (DDS) - Tyas Indah Twi Handayani; Jafar Sembiring; Arief Musta'in (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2018)
Telkom Divisi Digital Service (DDS) is a unit responsible for product innovations for Telkom. An internal survey conducted in June 2016 showed the lack of good understanding about the innovation process among employees. Entropy measurement showed that the organization culture categorized as “less than healthy”. Moreover, the implementation of virtual organization resulted in a lot of confusion among the employees. This research aimed to investigate the influence of Organization Culture variable and Organization Structure variable to the Innovation Process variable. Data were collected by distributing online questionnaires to 308 DDS employees and got 202 valid responses. Path analysis with SPSS showed that both Organization Culture and Organization Structure, either simultaneously or partially, had a positive influence toward Innovation Process. The Organizational Culture variable has a 37.27% influence towards Innovation Process variable, whereas the Organizational Structure variable has an 8.94% influence towards Innovation Process variable. In accordance with the research result, it is suggested that Telkom DDS focuses on the improvement of the organization culture to increase the innovation process. And for further research, it is recommended to explore other variables uncovered yet in this research, such as leadership within an organization, work environment, etc.